2019
DOI: 10.1051/matecconf/201926602005
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Impact of Aircraft Noise towards Residential Property Price

Abstract: The objective of this paper is to examine the effect of aircraft noise on residential property price within the case study area, and the main focus of this research was the distance of selected residential housed from Kuching International Airport (KIA). Aircraft noise is a source of noise pollution and act as environment factor that affect the house prices. Environmental disamenities from water and noise pollution will caused the houses to sell at lower price, accounted 20.8% less than houses located in area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…For the former, studies have found parks [24], trees [18], waterfronts [17,25,26], and landmark buildings [27,28] to be attractive to residents. Meanwhile, for the latter, studies have identified transportation infrastructure (such as airports, highways, and railways) [29,30] and municipal infrastructure (such as high-voltage corridors, substations, sewage treatment plants, landfill sites, and signal towers) [31,32], factories [33,34], and logistics centers and wholesale markets [34] to be repelling elements in residential location choices.…”
Section: Introductionmentioning
confidence: 99%
“…For the former, studies have found parks [24], trees [18], waterfronts [17,25,26], and landmark buildings [27,28] to be attractive to residents. Meanwhile, for the latter, studies have identified transportation infrastructure (such as airports, highways, and railways) [29,30] and municipal infrastructure (such as high-voltage corridors, substations, sewage treatment plants, landfill sites, and signal towers) [31,32], factories [33,34], and logistics centers and wholesale markets [34] to be repelling elements in residential location choices.…”
Section: Introductionmentioning
confidence: 99%